Spatial biology analysis reveals B cell follicles in secondary lymphoid structures may regulate anti-tumor responses at initial melanoma diagnosis - Therien, Aaron D.; Beasley, Georgia M.; Rhodin, Kristen E.; Farrow, Norma E.; Tyler, Douglas S.; Boczkowski, David; Al-Rohil, Rami N.; Holl, Eda K.; Nair, Smita K. (Frontiers in Immunology, 2022)
Introduction: B cells are key regulators of immune responses in melanoma. We aimed to explore differences in the histologic location and activation status of B cell follicles in sentinel lymph nodes (SLN) of melanoma patients. Methods: Flow cytometry was performed on fresh tumor draining lymph nodes (LN). Paraffin slides from a separate cohort underwent NanoString Digital Spatial Profiling (DSP). After staining with fluorescent markers for CD20 (B cells), CD3 (T cells), CD11c (antigen presenting cells) and a nuclear marker (tumor) was performed, regions of interest (ROI) were selected based on the location of B cell regions (germinal follicles). A panel of 68 proteins was then analyzed from the ROIs. Results: B cell percentage trended higher in patients with tumor in LN (n=3) compared to patients with nSLN (n=10) by flow cytometry. B cell regions from a separate cohort of patients with tumor in the (pSLN) (n=8) vs no tumor (nSLN) (n=16) were examined with DSP. Within B cell regions of the SLN, patients with pSLN had significantly higher expression of multiple activation markers including Ki-67 compared to nSLN patients. Among 4 patients with pSLN, we noted variability in arrangement of B cell follicles which were either surrounding the tumor deposit or appeared to be infiltrating the tumor. The B cell follicle infiltrative pattern was associated with prolonged recurrence free survival. Conclusion: These data suggest a role for B cell follicles in coordinating effective adaptive immune responses in melanoma when low volume metastatic disease is present in tumor draining LN.